Synergistic effect of binary metal doping and nanotechnology to boost the light-harvesting properties of rare earth metal oxide. Issue 1 (1st January 2023) - Ishfaq, Muhammad; Kousar, Tehmina; hussain, Mehtab; Somaily, Hamoud; Mubeen, Sidra; Potrich, Erich; Panduro-Tenazoa, Nadia Masaya; Salam, Mohamed Abdel; Ejaz, Syeda Rabia; Aadil, Muhammad
Abstract: Material scientists are currently focusing on employing photocatalytic materials to detoxify household and industrial waste to tackle rising water pollution problems. Narrow-bandgap materials are more valuable than other photocatalysts due to their visible light-harvesting characteristics. In this research, binary metal-doped cerium oxide (3 mol % Cd, 5 mol % Zn–CeO2 = CZC-1 and 5 mol % Cd, 3 mol % Zn–CeO2 = CZC-2) photocatalysts were successfully prepared through the facile and affordable co-precipitation method. The crystal structure, chemical functionality, morphology, composition, and optical behavior of the as-prepared binary metal-doped cerium oxide samples were explored via advanced physiochemical techniques. UV–Vis spectroscopy revealed that the CZC-2 photocatalyst possessed a relatively lower bandgap (2.15 eV) than the counterpart (CZC-1); hence it could be used as a visible-light triggered catalyst. The binary metal-doped photocatalyst's dye and microbe degradation efficacies were compared using methylene blue and P. Vulgaris, respectively. The CZC-2 photocatalyst showed superior dye degradation activity and mineralized almost 97% dye after 60 min irradiation time. Even after five reuse cycles, the recyclability tests showed that the catalytic efficiency of CZC-2 NPs only dropped by 4.5%. The CZC-2 photocatalyst's high photocatalytic activity and long-term stability show that the CZC-2 nanoarchitecture can be used in practical ways to clean up the environment. Graphical abstract: Image 1